PCR to CRISPR: Role of Nucleic Acid Tests (NAT) in detection of COVID-19 - Sikandar Hayat Khan; Zaidi, Sabeen Khursheed; Gilani, Mehreen (Journal of the Pakistan Medical Association, 2022)
COVID-19 infection has emerged as an unparalleled pandemic with morbidity and mortality tolls challenging diagnostic approaches and therapeutic interventions, and raising serious questions for healthcare policy-makers. From the diagnostic perspective, Reverse transcriptase polymerase chain reaction remains the gold standard. However, issues associated with gene primer variation in different countries, low analytical sensitivity, cross-reactivity with certain human coronaviruses have raised serious concerned within the scientific community. Alongside longer turnaround times, requirements of sophisticated equipment and trained technicians are the other challenges for conventional reverse transcriptase polymerase chain reaction testing. The recent biotechnological boom has now allowed newer nucleic acid testing options for diagnosing severe acute respiratory syndrome coronovairus 2 with much better diagnostic efficiency, reduced turnaround times and possible benefit for use as a point-of-care test. —Continue